2010
DOI: 10.1254/jphs.10r10fm
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs and Their Therapeutic Potential for Human Diseases: MiR-133a and Bronchial Smooth Muscle Hyperresponsiveness in Asthma

Abstract: Abstract. MicroRNAs (miRNAs) play important roles in normal and diseased cell functions. The small-GTPase RhoA is one of the key proteins of bronchial smooth muscle (BSM) contraction, and an upregulation of RhoA has been demonstrated in BSMs of experimental asthma. Although the mechanism of RhoA upregulation in the diseased BSMs is not fully understood, recent observations suggest that RhoA translation is controlled by a miRNA, miR-133a, in cardiomyocytes. Similarly, in human BSM cells (hBSMCs), our recent stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(45 citation statements)
references
References 43 publications
1
43
0
1
Order By: Relevance
“…The IL-13-induced upregulation of RhoA mRNA was abolished by coincubation with a STAT6 inhibitor, whereas, interestingly, this treatment had no effect on the downregulation of miR-133a induced by IL-13 (54). These observations suggest that IL-13 is capable of induction of RhoA protein upregulation both by increasing RhoA mRNA via a STAT6-dependent mechanism and by increasing RhoA translation via the STAT6-independent downregulation of miR-133a in hBSMCs (79). Previous evidence that IL-13 is a key factor for induction of bronchial smooth muscle hyperresponsiveness and upregulation of RhoA protein in a mouse model of allergic bronchial asthma (52) reminds us that miR-133a might also be downregulated in bronchial smooth muscles of the diseased animals.…”
Section: Post-transcriptional Regulation Of the Rhoa Genementioning
confidence: 82%
“…The IL-13-induced upregulation of RhoA mRNA was abolished by coincubation with a STAT6 inhibitor, whereas, interestingly, this treatment had no effect on the downregulation of miR-133a induced by IL-13 (54). These observations suggest that IL-13 is capable of induction of RhoA protein upregulation both by increasing RhoA mRNA via a STAT6-dependent mechanism and by increasing RhoA translation via the STAT6-independent downregulation of miR-133a in hBSMCs (79). Previous evidence that IL-13 is a key factor for induction of bronchial smooth muscle hyperresponsiveness and upregulation of RhoA protein in a mouse model of allergic bronchial asthma (52) reminds us that miR-133a might also be downregulated in bronchial smooth muscles of the diseased animals.…”
Section: Post-transcriptional Regulation Of the Rhoa Genementioning
confidence: 82%
“…MiRNAs may regulate up to one-third of all protein coding genes in the human genome (46), and the relevance of miRNAs in asthma has been previously implied in studies of their expression in human asthma and animal models of allergic airway inflammation (47)(48)(49)(50)(51)(52). We performed miRNA microarrays on AMs from healthy subjects and patients with asthma, and performed bioinformatics analyses followed by qPCR confirmation of the in silico results.…”
Section: Discussionmentioning
confidence: 99%
“…We demonstrated that inhibition of miRNA-221 resulted in the reduction of inflammatory cell infiltration. It has been reported that mice deficient in miRNA-155 display increased lung airway remodeling [6], that inhibition of miRNA-126 suppresses airway hyperresponsiveness and airway inflammation [10], that miRNA-26a regulates airway smooth muscle hypertrophy [11], that let-7 miRNA promotes inflammation in asthma [12], and that miRNA-133a leads to bronchial smooth muscle hyperresponsiveness [13]. miRNA-221 is another important miRNA that participates in the pathogenesis of asthma and is essential in the development of airway inflammation in allergic asthma.…”
Section: Discussionmentioning
confidence: 99%
“…miRNA-26a has been demonstrated to act as a regulatory factor in airway smooth muscle hypertrophy [11], while let-7 miRNA has been revealed to promote the inflammation associated with asthma [12]. miRNA-133a acts to negatively regulate the expression of RhoA, the action of which results in bronchial smooth muscle hyperresponsiveness [13].…”
Section: Introductionmentioning
confidence: 99%